THE IMPACT OF CONTEXTUAL TEACHING AND LEARNING APPROACH ON CREATIVE THINKING ABILITIES IN ESSENTIAL GRADE IV INPRES TAMAMAUNG III MAKASSAR CITY - Yulianti, Tri; Nursalam, Nursalam; Jamaluddin, Jamaluddin (Conciencia, 2023)
This study uses quantitative research with a quasi-experiment. It aims to determine the effect of using the Contextual Teaching and Learning (CTL) approach on students' creative thinking skills. The design used was a post-test-only control group design. This research was conducted in class IV UPT SPF SD Inpres Tamamaung III Makassar City, Even Semester, 2022/2023 Academic Year. The population in this study were all students of SD Inpres Tamamaung III Makassar City. The sampling technique in this study used the Simple Random Sampling technique. The sample in this study in the experimental class was Class IVA, which amounted to 25 students, and the control class was class IVB, which amounted to 25 students. The research instruments were observation sheets, questionnaires, and learning outcomes tests. Data analysis techniques using descriptive statistics and inferential statistics. 1) The Contextual Teaching Learning (CTL) approach affects the creative thinking ability of fourth-grade students of SD Inpres Tamamaung III Makassar City.